Interim recommendations for the use of the Janssen Ad26.COV2.S (COVID-19) vaccine : interim guidance, first issued 17 March 2021, updated 15 June 2021, updated 9 December 2021, updated 6 June 2022 (World Health Organization, 2022)
These WHO interim recommendations on the use of the Janssen Ad26.COV2.S (COVID-19) vaccine were developed on the basis of advice issued by the Strategic Advisory Group of Experts on Immunization (SAGE).
Keywords: Disease Outbreaks; COVID-19; vakcíny proti COVID-19; veřejné zdravotnictví; COVID-19 Vaccines; infekční lékařství; Betacoronavirus; preventivní medicína; epidemický výskyt choroby